Research of the Backlash Analysis and Experimental Test for RV Reducer - Zhang Jie; Wan Huayun; Shi Xiang; Shi Xudong; Wei Yuncheng (Jixie chuandong)
Taking the homemade high precision RV reducer as study object,According to the characteristics of the transmission principle and structure,by using the sensitivity index analysis,the parameter optimization design of the RV reducer is carried out,the theoretical value of geometry backlash of theory reducer is obtained,the effectiveness of the proposed method is verified by experiment. The study results show that,the calculated value of theoretical geometric backlash is 0. 397’ 0. 859’,and the backlash of experiment test is0. 93’. The test results are verified through the experiment and theory calculation results contrast analysis,the homemade RV reducer can meet the using requirement of the reducer. A theoretical basis for the research and development of RV reducer is provided by this study.